ANALYSIS OF BALLISTIC ELECTRON TRANSPORT IN DOUBLE-GATE MOSFET USING THE NON-EQUILIBRIUM GREENâS FUNCTION METHOD - Charity Sangian, Messiah
This study analyzes ballistic electron transport in Double-Gate (DG) Metal-OxideSemiconductor Field Effect Transistor (MOSFET) using the Non-Equilibrium Green's Function (NEGF) method combined with the Newton-Raphson technique to solve the Schrödinger and Poisson equations. The research aims to understand the influence of external voltage on the distribution of electrostatic potential, subband energy, and electron density, as well as its impact on channel conductivity in nanoscale transistors. Simulation results reveal that the electrostatic potential distribution plays a crucial role in controlling electron movement. A gradual increase in gate-source (????????????) and drain-source (????????????) voltages lowers the potential barrier near the source and drain, enabling electron accumulation in the channel and enhancing conductivity, which subsequently generates current. Subband energy analysis reveals that the first subband dominates electron flow, while higher-energy subbands are only occupied under larger external bias conditions. The electron density distribution indicates a high concentration of electrons in the source and drain regions, while the channel approaches zero at higher-energy subbands. Under low voltage conditions, the electron distribution is dominated by the first subband, whereas the contributions of the second and third subbands become significant at higher gate voltages.